STANDAR OPERASIONAL PROSEDUR ROOM SERVICE AMAROOSSA HOTEL BANDUNG - Panji Septian Derianto; Yuliana Pinaringsih Kristiutami (LPPM Universitas Bina Sarana Informatika, 2015)
Abstract - Tourism is everything that is related to and associated with the business needs someone to travel. And each traveler typically require service facilities to rest and service for food and beverages. Every hotel both large and small certainly has a restaurant and bar on the ground guests can enjoy food and drinks, while for guests who wish to enjoy food and drink in your own room is also equipped with service facilities room service. Room service department operates for 24 hours to serve guests by serving meals like breakfast, lunch, dinner and supper. Room service at Amarossa Hotel has standard operating procedures have been established. Methods of research by the author is to perform observation / research, interviews, documentation and literature. Standard operating procedure is executed in Amarossa hotel room service department that receives oderan of the phone, making captain orders, prepare the equipment, orders delivered back to the room guests. Keywords: Standard Operating Procedure, Room Service, hotel Abstrak - Pariwisata adalah segala sesuatu yang menyangkut dan berhubungan dengan urusan kebutuhan seseorang melakukan perjalanan. Setiap traveler membutuhkan fasilitas pelayanan untuk beristirahat serta pelayanan untuk makanan dan minuman. Hotel besar maupun kecil pasti memiliki restoran dan bar. Tamu yang ingin menikmati makanan dan minuman dikamar sendiri juga di lengkapi dengan fasilitas pelayanan room service. Room service department ini beroperasi selama 24 jam untuk melayani para tamu hotel dengan menyajikan makanan seperti breakfast, lunch, dinner dan juga supper. Room service di Amaroossa Hotel memiliki standar operasional prosedur yang telah ditetapkan. Metode penelitian yang dilakukan penulis adalah dengan melakukan obeservasi/riset, wawancara, dokumentasi dan juga studi pustaka. Standar operasional prosedur yang dijalankan di Amaroossa Hotel pada departement room service yaitu menerima oderan dari telepon, membuat captain order, mempersiapkan peralatan, pesanan diantar ke kamar tamu. Kata Kunci: Standar Operasional Prosedur, Room Service, hotel